2016
DOI: 10.3892/ijo.2016.3621
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone downregulates expression of carbonic anhydrase IX via HIF-1α and NF-κB-dependent mechanisms

Abstract: Dexamethasone is a synthetic glucocorticoid frequently used to suppress side-effects of anticancer chemotherapy. In the present study, we showed that dexamethasone treatment leads to concentration-dependent downregulation of cancer-associated marker, carbonic anhydrase IX (CA IX), at the level of promoter activity, mRNA and protein expression in 2D and 3D cancer cell models. The effect of dexamethasone on CA IX expression under hypoxic conditions is predominantly mediated by impaired transcriptional activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…Tumor hypoxia promotes invasiveness and is associated with resistance to chemotherapeutics and radiation and thus poor prognosis [ 1 5 ]. Human carbonic anhydrase IX (CA IX) shows limited expression in normal tissues [ 6 ] and is significantly up-regulated by hypoxia-inducible factor 1α (HIF-1α) [ 7 ] or other alternative microenvironmental factors [ 8 12 ] in a variety of tumors. CA IX is crucial for cancer cell survival because bicarbonate and protons, produced upon CA IX-catalyzed reversible hydration of CO 2 , are necessary to maintain the cellular pH balance: bicarbonate is transported into the cell to neutralize intracellular acid, while protons increase extracellular acidification [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor hypoxia promotes invasiveness and is associated with resistance to chemotherapeutics and radiation and thus poor prognosis [ 1 5 ]. Human carbonic anhydrase IX (CA IX) shows limited expression in normal tissues [ 6 ] and is significantly up-regulated by hypoxia-inducible factor 1α (HIF-1α) [ 7 ] or other alternative microenvironmental factors [ 8 12 ] in a variety of tumors. CA IX is crucial for cancer cell survival because bicarbonate and protons, produced upon CA IX-catalyzed reversible hydration of CO 2 , are necessary to maintain the cellular pH balance: bicarbonate is transported into the cell to neutralize intracellular acid, while protons increase extracellular acidification [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the limited stability of HIF-1α could mask its effective role in hMSCs during a prolonged biological process, such as osteogenic terminal differentiation. Moreover, even if the interplay between glucocorticoid and HIF-1α in hypoxic areas remains unclear, many evidences demonstrated that dexamethasone reduces protein level of HIF-1α as well as its activity affecting transcription of HIF-1α target genes [50,51]. Therefore, we cannot exclude that long-term hypoxic treatment in vitro can lead to results that are difficult to explain when hMSCs are induced to differentiate toward the osteogenic lineage by the conventional dexamethasone-added osteogenic medium.…”
Section: Discussionmentioning
confidence: 96%
“…Degradation of IκB leads to the activation of the pathway, resulting in the nuclear translocation of the NF-κB complexes (32). In the nucleus, activated NF-κB binds to the specific DnA sequence called response element in the promoter region of a number of target genes including cytokines, chemokines, adhesion molecules as well as angiogenic factors and key enzymes, and subsequently regulates tumor initiation and progression (33). The promotion of NF-κB pathway increases the metastatic activity of cancer cells by upregulating u-PA and MMPs (34).…”
Section: Discussionmentioning
confidence: 99%